(untitled) (Research, Society and Development, 2022)
Objective: The present study intended to analyze the effects of a relaxation technique called autogenic training, on nonlinear heart rate variability, with the hypothesis that the relaxation in question is capable of promote greater synergism between the sympathetic and the parasympathetic nervous system, thus avoiding high levels of stress and future complications. Methods: To this end, a controlled, non-randomized, open and cross-sectional clinical study was conducted, with 19 participants who underwent a single session of autogenic training. Results: The results show that both groups (experimental and placebo) had p-value<0.05 and sometimes marginally significant. This consequence instigates the following question: does autogenic training AT provide a state of relaxation only by reason of the placebo effect? Conclusion: According to the study, it is concluded that during the autogenic training there was no increase in the chaotic response, in addition to no improvement in the synergism between the sympathetic and the parasympathetic nervous system.